THEORETICAL JUSTIFICATION OF ECONOMIC PRECONDITIONS FORMING LONG-TERM CAP RATES CHANGES TRENDS - Поздняков, Юрій; Лапішко, Марія (Socio-economic relations in the digital society, 2019)
The paper considers the capitalization rate changes long-term trends formation features on the domestic real estate market in the conditions of the economic crisis. The factors infl uencing the growth of uncertainty of these market indicators are revealed and analyzed. Th e theoretical principles of value formation market mechanisms functioning in unbalanced real estate market situation are investigated. The current market trends are identifi ed and summarized. Some forecasts of further market characteristics changes, based on this analysis, are formulated. It is shown that in today’s Ukraine conditions the commercial banks foreign currency deposits rates are only formally and nominally risk-free, as they contain a number of rather high country investment risks. For countries with stable economic growth, these country risks are zero or close to zero, and their rates of foreign currency deposits are practically equal to the value of the actual risk-free rate. In the paper is established and generalized some earlier studies by the authors results proved the fact of using the components of the total premium for risk at more than double the size in the calculation of actual capitalization rate in the  Ukrainian economy current conditions. The generalization of the capitalization rate changes long-term trends in market characteristics observed during the Ukrainian economic crisis development, is carried out in residential and commercial real estate market segments information base, the price indexes of which was determined by independent expert evaluation methods. Practical recommendations for the evaluation results accuracy and reliability increasing are formulated.
Keywords: real estate appraising; market value; capitalization rate; appraising error; appraising accuracy; time value of money